Climate Services for Agriculture in Rwanda: Initial findings from PICSA monitoring and evaluation - Clarkson, Graham; Dorward, Peter; Kagabo, Desire M.; Nsengiyumva, Gloriose (2017)
Participatory Integrated Climate Services for Agriculture (PICSA) is an approach that seeks to build resilience at the farm level by supporting decision-making through the integration of information on location-specific climate, crops, livestock, and livelihoods. It emphasizes practical hands-on methods that can easily be used and understood by farmers by integrating livelihood alternatives to those on-farm. PICSA is led by the University of Reading (UoR) based in the UK, and has been supported by the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS). More than 2,600 farmers have been trained in the first year rolling out PICSA in Rwanda. Farmers find the different elements of the PICSA approach useful and are using them in their decision-making processes, namely (e.g. historical climate information [99%], participatory budgets, and seasonal forecast. As a result of the PICSA training and the information shared, tThe vast majority of those farmers are making changes in their crops, livestock, and/or livelihood enterprises. Farmers are sharing the different PICSA tools and information with their peers.